Software Technologies : 13th International Conference, ICSOFT 2018, Porto, Portugal, July 26-28, 2018, Revised Selected Papers /: 13th International Conference, ICSOFT 2018, Porto, Portugal, July 26-28, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available